The Self as the Spiritual Subject. An Overview of Selected Concepts in View of the Positivist Paradigm - Jastrzębski, Andrzej (Verbum Vitae, 2022)
The main predicament presented in this article lies in the complexity found in the internal structure of the human being when one searches for key elements that define its essence and uniqueness. The overview begins with empirical research as exemplified in psychology, continues in presenting chosen theories in modern philosophy, with an accent on the phenomenological method, and subsequently puts forward the synthesis of them both in psychotherapy. The last part is dedicated to theology as a distinct way to uncover what the essence of being human is, as based on divine Revelation; the latter is the only one of the presented sciences to be explicitly aware of the source of the mystery at the basis of being human. This article attempts to compare the research end results of chosen approaches by demonstrating their relationship to the most hidden aspects of being human. The analysis is organized around the concept of recognizing and accepting the place of mystery in the understanding of what are the most essential elements in the human being. As a result, psychology is conceptualized as a science that does not allow mystery; theology, however, is found to underline the presence of mystery in relationship to our divine origins.